Queuosine‐tRNA promotes sex‐dependent learning and memory formation by maintaining codon‐biased translation elongation speed - Cirzi, Cansu; Dyckow, Julia; Legrand, Carine; Schott, Johanna; Guo, Wei; Perez Hernandez, Daniel; Hisaoka, Miharu; Parlato, Rosanna; Pitzer, Claudia; van der Hoeven, Franciscus; Dittmar, Gunnar; Helm, Mark; et al. (The EMBO journal, 2023)
Queuosine (Q) is a modified nucleoside at the wobble position of specific tRNAs. In mammals, queuosinylation is facilitated by queuine uptake from the gut microbiota and is introduced into tRNA by the QTRT1‐QTRT2 enzyme complex. By establishing a Qtrt1 knockout mouse model, we discovered that the loss of Q‐tRNA leads to learning and memory deficits. Ribo‐Seq analysis in the hippocampus of Qtrt1‐deficient mice revealed not only stalling of ribosomes on Q‐decoded codons, but also a global imbalance in translation elongation speed between codons that engage in weak and strong interactions with their cognate anticodons. While Q‐dependent molecular and behavioral phenotypes were identified in both sexes, female mice were affected more severely than males. Proteomics analysis confirmed deregulation of synaptogenesis and neuronal morphology. Together, our findings provide a link between tRNA modification and brain functions and reveal an unexpected role of protein synthesis in sex‐dependent cognitive performance.
Gesehen am 24.07.2024